Controversias sobre la ampliación de plazo en el marco de la obra pública - García Valdez, Leandro (2023)
In this paper, the author presents a logbook on the current state of controversies related to requests for extension of time in the framework of public works. Firstly, the general aspects of this legal remedy are explained. Secondly, the main controversies arising in arbitral proceedings are commented on, based on the contrast between the position that some public entities usually take to deny an extension of time, as opposed to what is regulated in the law, what is developed by doctrine and what is resolved in arbitral awards. The aim is to verify the basis of what is stated by public entities.